Representation of Javanese Beliefs in the Film Sumala (2024):Magical Realism - Oktaviona, Anindya; Suaedi, Hasan; Dzarna, Dzarna (Journal of Language and Literature Studies, 2025)
The phenomenon of the representation of local beliefs in modern Indonesian films shows a tendency to combine traditional elements with contemporary storytelling styles, but studies that specifically examine this combination through the perspective of magical realism are still limited. This study aims to reveal how the film Sumala  (2024) represents Javanese beliefs through three main elements of magical realism according to Wendy B. Faris, namely the irreducible element, merging realms, and disruptions of time, space, and identity. The study uses a qualitative descriptive method with data sources in the form of scenes, Dialogues, and visual symbols in the film. Data are analyzed through a process of reduction, classification, interpretation, and drawing conclusions based on the theory of magical realism and the concept of Javanese beliefs. The results show that Sumala presents magical objects, spiritual rituals, and human interactions with spirits as magical elements that are naturally accepted in the story world. This representation illustrates the Javanese view of life that emphasizes the balance between the rough universe and the subtle universe as an important part of the cosmological order. This study concludes that the magical elements in Sumala not only function as narrative aesthetics but also play an important role in preserving Javanese spiritual and cultural values. This finding has implications for strengthening film and cultural studies, particularly regarding the representation of local wisdom in modern Indonesian cinema.